PREVENTING FRAUD IN LOCAL GOVERNMENT: THE MODERATING ROLE OF INTERNAL CONTROL - Priyangga, Bangkit Aknico; Ratnawati, Vince; Taufik, Taufeni (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to analyze the impact of organizational culture, individual morality, and whistleblowing systems on fraud prevention, with internal control serving as a moderating variable within the Regional Apparatus Organizations (OPD) of the Riau Provincial Government. Employing a quantitative methodology, the research gathers primary data through the administration of questionnaires. The population under consideration comprises 34 OPDs within the Riau Provincial Government, utilizing purposive sampling as the selection technique. A total of 102 respondents were chosen based on specified characteristics. Data analysis was conducted using SmartPLS version 4 software. The findings indicate that both organizational culture and the whistleblowing system exert a significant influence on fraud prevention, whereas individual morality does not demonstrate a statistically significant effect. Additionally, internal control is shown to enhance the impact of individual morality and the whistleblowing system on fraud prevention, while it does not strengthen the effect of organizational culture in this regard. These results offer practical implications for local governments aiming to fortify ethical and moral standards, as well as implement robust internal controls, thereby minimizing the risk of fraud. The implementation of these strategies is anticipated to reduce the underlying causes of fraudulent behavior in the public sector.